(untitled) - Moskowitz, Jeremy (Indianapolis, Ind, 2007)
Presenting a fully updated resource for Windows Vista that shows you how best to use Group Policy in order to take full advantage of Active Directory and create a managed desktop environment. You’ll learn details about the GPMC, Group Policy troubleshooting techniques, and configuring Group Policy to create a resilient desktop environment. You’ll also discover how to create and manage ADMX files and leverage the Group Policy Central Store as well as deploy Office 2007, Office 2003, and more using Group Policy Software Installation.
Keywords: Operating systems (Computers),Hệ điều hành máy tính